2003
DOI: 10.1590/s1516-89132003000200020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water renewal rates on the reproductive and molting cycles of Penaeus paulensis in captivity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Studies on the relationship between molt cycle and reproductive performance could improve the planning of nauplii production in captivity. Reproduction of unilaterally eyestalkablated F. paulensis in relation to its molt cycle in a continuous water flow or a batch renewal maturation system was analyzed by Peixoto et al (2003c). Results indicated that the intermolt period of females and males (17.4 ± 3.2 and 17.8 ± 4.6 days, respectively), number of days between molts and first spawn (6.9 ± 2.8 days) and number of spawns in the intermolt period (1.4 ± 0.5), were not significantly different between the maturation systems.…”
Section: And Molting Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the relationship between molt cycle and reproductive performance could improve the planning of nauplii production in captivity. Reproduction of unilaterally eyestalkablated F. paulensis in relation to its molt cycle in a continuous water flow or a batch renewal maturation system was analyzed by Peixoto et al (2003c). Results indicated that the intermolt period of females and males (17.4 ± 3.2 and 17.8 ± 4.6 days, respectively), number of days between molts and first spawn (6.9 ± 2.8 days) and number of spawns in the intermolt period (1.4 ± 0.5), were not significantly different between the maturation systems.…”
Section: And Molting Cyclesmentioning
confidence: 99%
“…Therefore, male to female ratios ranging from 1:1 to 1:1.5 and stocking densities from 5 to 7 animals/m 2 have been commonly employed for F. paulensis. Poor mating success was also associated with the small size of experimental maturation tanks (Peixoto et al, 2003c). However, descriptions of mating behavior for this species suggested that tank size did not play a significant role as females tended to stay on the bottom and did not swim before and during copulation (Brisson, 1985).…”
Section: Maturation and Spawningmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the supposedly advantageous performance of wild broodstock, the unpredictable supply and high capture costs might constrain the sustainable development of F. paulensis farming in the region. In this context, several studies have been carried out to optimize the maturation and reproduction of this species in captivity (Peixoto et al, 2002a(Peixoto et al, , 2002b(Peixoto et al, , 2003b(Peixoto et al, , 2003c(Peixoto et al, , 2004b, especially the evaluation of the domesticated broodstock as an alternative (Cavalli et al, 1997;Peixoto et al, 2003aPeixoto et al, , 2004a. The accelerated search to close the life cycle and improve the reproductive performance of F. paulensis in captivity will certainly contribute to the design of an efficient breeding program.…”
Section: Availability Of Plmentioning
confidence: 99%
“…captura do camarão-rosa é a principal fonte de renda para a população de pescadores artesanais, os quais também vêm sendo beneficiados com a criação da espécie em estruturas alternativas (cercados e gaiolas) e viveiros nesta região (WASIELESKY et al, 2002, PEIXOTO et al, 2003PRETO et al, 2005, KRUMMENAUER et al, 2006. Embora a produção em cativeiro de pós-larvas de F. paulensis seja uma realidade, freqüentemente ocorre diminuição na taxa de fertilização dos ovos, atribuídas à ausência de cópula nos tanques de maturação, resultando em perdas na produção (PEIXOTO et al, 2004a).…”
unclassified